Translation and cross-cultural adaptation of the Detailed Assessment of Speed of Handwriting 17+ to Brazilian Portuguese: Conceptual, item and semantic equivalence - Cardoso, Monique Herrera [UNESP]; Capellini, Simone Aparecida [UNESP] (FapUNIFESP (SciELO), 2018)
Purpose: Perform a cross-cultural adaptation of the Detailed Assessment of Speed of Handwriting 17+ (DASH 17+) for Brazilians. Methods: Evaluation of (1) conceptual, item and (2) semantic equivalence, with assistance of four translators and application of a pilot study to 36 students. Results: (1) The concepts and items are equivalent in the British and Brazilian cultures. (2) Adaptations were made concerning the English language pangram used in copying tasks and selection of the lower-case, cursive handwriting in the alphabet-writing task. Application of the pilot study verified acceptability and understanding of the proposed tasks by the students. Conclusion: The Brazilian Portuguese version of the DASH 17+ was presented after finalization of the conceptual, item and semantic equivalence of the instrument. Further studies on psychometric properties should be conducted with the purpose of measuring the speed of handwriting in youngsters and adults with greater reliability and validity to the procedure.
Keywords: Assessment; Cultural adaptation; Handwriting; Language and hearing; Sciences; Speech; Translation